Risk of major congenital malformations following first‐trimester exposure to vaginal azoles used for treating vulvovaginal candidiasis: a population‐based retrospective cohort study. (25th June 2018) - Rotem, R; Fishman, B; Daniel, S; Koren, G; Lunenfeld, E; Levy, A
Abstract : Objective: To evaluate the risk for major malformations following first‐trimester exposure to vaginal azoles. Design: A population‐based retrospective cohort study of women exposed to vaginal azoles from the first day of the last menstrual period until the 90th gestational day. Setting: A combination of four computerised databases: medications, birth, infant hospitalizations, and pregnancy terminations. Population: All women who gave birth or underwent a pregnancy termination at Soroka Medical Center, Beer‐Sheva, Israel, between 1999 and 2009. Methods: Crude and adjusted relative risks for major congenital malformations and for specific malformations according to organ systems were calculated using a multivariate negative binomial regression. Potential confounders were assessed and controlled for included parity, maternal age, ethnicity, maternal diabetes, smoking, and year of birth or pregnancy termination. Additional analysis using propensity score matching was performed for selected malformations. Main outcome measures: Major malformations as well as specific malformations according to organ systems. Results: Of 101 615 pregnancies, 1993 (1.96%) were exposed to clotrimazole vaginal tablets and 313 (0.31%) to miconazole vaginal tablets during the first trimester of pregnancy. No association was found between first‐trimester exposure to clotrimazole and major or specific malformations. An association was found between miconazole exposure and musculoskeletal malformation in general and other congenital musculoskeletal anomalies in particular. However, no association was detected when propensity score matching was used. Conclusions: Intrauterine exposure to vaginal azoles during the first trimester of pregnancy was not associated with either major or specific malformations according to organ systems. Tweetable abstract: First‐trimester exposure to vaginal azoles is not associated with either major or specific malformations. Tweetable abstract: First‐trimester exposure to vaginal azoles is not associated with either major or specific malformations.